Laboratorio interactivo de cultivos agrícolas (2021)
This partial plan arises from the need to help the ecosystems that have been affected over time and have not been recovered by society and thus rescue all the hydric zones and the diversity of flora and fauna that this corridor contemplates from Girardot to Cajamarca and its surroundings. Everything arises thanks to some analyzes that were carried out at the country, region and city level where important factors were observed such as their hydrography, natural reserves, ecosystems, cultures, productivity, uses, ecological structures and public space, thus generating conclusions that were taken to our problem that has been the social and environmental sphere.